Connecting Supervisor Procedural Justice to Perceived Tensions With Litigants Among Chinese Judges - Ding, Yao (Criminal justice and behavior, 2024)
Recent literature on procedural justice has consistently shown positive organizational outcomes resulting from fair and just treatment by supervisors. This study expands the current literature by assessing the beneficial effect of being treated fairly and justly by supervisors in court settings. Based on survey data from Chinese judges, this study analyzes the direct linkage between supervisor procedural justice and judges’ perceived tensions with litigants and their indirect relationship through trust in litigants and external procedural justice. The results of structural equation modeling indicate that supervisor justice is positively related to trust in litigants and external procedural justice and negatively associated with tensions with litigants. The indirect connection between supervisor justice and tensions with litigants is mainly through external procedural justice. Female and seasoned judges are more willing than their male and less-experienced counterparts to treat litigants in a procedurally just manner.